Social And Politic Islam - Armanusah Fazira Sudarmansyah (Proceeding International Seminar of Islamic Studies, 2019)
This paper traces the  roots of the  emergence of Islamic religious and political movements in Indonesia especially during and after  their depoliticization during the New Order regime. There were two important impacts of the depoliticization, first, the emergence of various study groups and student organizations in university campuses. Second, the emergence of Islamic political parties   after    thefall   of   Suharto.  In   addition,   political   freedom  after    long oppression also helped create religious groups both  radical  on the one hand  and liberal  on  the  other.  These radical  and  liberal  groups were  not  only intellectual movements  but   also  social  and   political   in  nature.  Although   the   present confrontation  between  liberal  and   moderate  Muslims  could   lead   to  serious conflict  in the  future, and  would  put the  democratic atmosphere at risk, the  role of the  majority  of the  moderates remains decisive in determining the  course of Islam and politics in Indonesia.